2007
DOI: 10.1007/s10509-007-9373-3
|View full text |Cite
|
Sign up to set email alerts
|

Short time scale pulse stability of the Crab pulsar in the optical band

Abstract: The fine structure and the variations of the optical pulse shape and phase of the Crab pulsar are studied on various time scales. The observations have been carried out on 4-m William Hershel and 6-m BTA telescopes with APD photon counter, photomultiplier based 4-channel photometer and PSD based panoramic spectrophotopolarimeter with 1 µs time resolution in 1994, 1999, 2003 and 2005-2006 years. The upper limit on the pulsar precession on Dec 2, 1999 is placed in the 10 s-2 hr time range. The evidence of a va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
(17 reference statements)
2
5
1
Order By: Relevance
“…Our results for the stability of the pulse profile (differences of up to ∼10 µs on a time scale of a day and even smaller variations on a time scale of less than a day; see Fig. 4) are not consistent with the results from Karpov et al (2007) who present variations of up to ∼150 µs in a fraction of a day. However, this variation is only present in a small part of their data set (December 2005 and January 2006), while the remainder of their data (obtained in December 1994and 1999, and November 2003 do not show substantial variations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results for the stability of the pulse profile (differences of up to ∼10 µs on a time scale of a day and even smaller variations on a time scale of less than a day; see Fig. 4) are not consistent with the results from Karpov et al (2007) who present variations of up to ∼150 µs in a fraction of a day. However, this variation is only present in a small part of their data set (December 2005 and January 2006), while the remainder of their data (obtained in December 1994and 1999, and November 2003 do not show substantial variations.…”
Section: Discussioncontrasting
confidence: 99%
“…We consider it unlikely that this night-to-night variation is solely caused by variations in the DM, since a variation of ∼1 times that of typical monthly variations is needed in 1 day. Variations in the peak position on time scales of days and shorter are studied in more detail by Karpov et al (2007), who find, during one observation, variations at the ∼150 μs-level.…”
Section: Optical-radio Lagmentioning
confidence: 99%
“…the pulse shape agrees well with the 33-year-old pulse profile obtained by Groth (1975), as well as with the more recent one by Karpov et al (2007).…”
Section: Resultssupporting
confidence: 88%
“…It is characterized by a double-peak folded profile, separated E-mail: luca.zampieri@oapd.inaf.it in phase by ∼ 0.4 (or ∼ 140 0 ). It is very stable (Zampieri et al 2011), although marginal evidence for a secular decrease in luminosity (Nasuti et al 1996) and weak variations in the pulse shape (Karpov et al 2007) have been reported.…”
Section: Introductionmentioning
confidence: 98%